Prisoners with disabilities in the Polish penitentiary system - NYMŚ-GÓRNA, AGNIESZKA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Agnieszka Nymś-Górna, Prisoners with disabilities in the Polish penitentiary system. Interdisciplinary Contexts of Special Pedagogy, no. 24, Poznań 2019. Pp. 177-187. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2019.24.10 The article deals with the subject of both intellectually and physically disabled prisoners. It describes people with disabilities, the functioning of the therapeutic system for prisoners and the situation of detaining people with disabilities in penitentiary isolation. The text aims to sensitise this issue and to identify this problem in the organisation of the penitentiary system.